The appellatives in intra-city named Kharkiv - Удовенко, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article deals with the appellative of Kharkov, which became proper names of road and street network of the city. The author has identified the main groups of urbanity Kharkiv to their values, established cases of the category outside the system of Kharkiv toponymy and made a conclusion on future directions for the study of urban toponymy in the city.